Fulminant Orbital Cellulitis – A Rare Presentation of Endogenous Endophthalmitis - Sharma, Unnati; Goel, Itisha; Chhabra, Simran; Gupta, Suresh Kumar; Gupta, Gayana (Nepalese Journal of Ophthalmology, 2023)
Background: Endogenous endophthalmitis refers to the intraocular infection resulting via haematogenous spread from the distant foci. Dengue is an important health problem in India with varied ophthalmic manifestations either due to viremia, immunologic phenomenon, or haemorrhagic tendency. Case: We report an unusual presentation of endogenous endophthalmitis as fulminant orbital cellulitis in a young adult patient having a history of dengue fever. Observations: Young male having history of dengue fever presented with complaints of sudden pain, swelling, redness, and loss of vision in the left eye. His clinical features and radiographic examination were suggestive of orbital cellulitis with pan-ophthalmitis, which rapidly progressed to endophthalmitis. Conclusion: This case highlights the role of orbital vessels as a possible route for occurrence of endophthalmitis in a case of orbital cellulitis.